Predictors of mobile internet usage in 10 African countries - Enrico Calandro; Rong Wang (International Telecommunications Society (ITS), 2012)
Mobile phones and Internet use can enable human capabilities that can contribute to positive developmental outcomes (Smith, Spencer, & Rashid, 2011; Ndung'u & Waema, 2011; Agüero, de Silva & Kang, 2011; Sen, 1999). Communication networks, in Africa particularly mobile phones, have been recognised as an important component for social mobilisation (Castells, 2009). Reports have focused on the role of mobile phones in organising social protests and political mobilization (Comninos, 2011) such as the food protest in Mozambique in 2007/08, and violent ethnic mobilisation in Kenya in 2009 and around the world. Further, since the Arab Spring, the use of the mobile phone for social mobilization has become an increasing focus of research. As part of this research which seeks to explore the role of ICTs in contemporary social and political engagement, this paper presents an empirical assessment of predominant social and demographic factors that are predictors of mobile Internet usage. It is based on nationally representative ICT household survey data collected by Research ICT Africa in 2011 and 2012 across 10 African countries. This study draws on previous studies on technology adoption, and tests on the effect of social factors and demographic variables on mobile Internet usage. Also, it presents descriptive data on network exposure. It poses the following research questions: what are the social aspects and demographic factors influencing mobile Internet usage in selected African countries? To what extent does belonging to specific civic affiliations such as religious, recreational or political groups impact on mobile Internet usage? The odd of using mobile Internet is assessed against demographic factors such as age, gender, income and level of education, among others. The impact of mobile Internet usage for social mobilisation is evaluated against belonging to specific social affiliations such as religious, recreational or political organisations. Other predictors include affiliation with certain social groups and the closeness of the local community. Network exposure was measured in the ICT household surveys, by asking respondents to list how many people out of their top five contacts are users of mobile phones and social network sites. Further, the analysis includes also an assessment of whether the use of the mobile phone increased or decreased contacts with specific social groups. What activities users got involved in through the mobile are also included into the analysis. The study concludes with policy implications on mobile Internet usage in African countries in particular related to democracy, empowerment and capability development. Furthermore, since it investigates whether mobile Internet usage enhances contacts with different social groups such as family, friends, religious or political groups, this study seeks to assess the potential of the technology to mobilise different networks in selected African countries.
Keywords: 330; ICT indicators; Access; Mobile Internet; Social Media; ICT Household Survey; ICTD